Clinical Practice Guideline: Bell's Palsy. (23rd August 2013) - Baugh, Reginald F.; Basura, Gregory J.; Ishii, Lisa; Schwartz, Seth R.
Abstract : Program Description: This miniseminar will consist of a lively panel discussion on the evidence‐based recommendations for the treatment and management of Bell's palsy as outlined in the recently published AAO‐HNS Clinical Practice Guideline. The guideline seeks to improve the quality of and reduce variation in the care Bell's palsy patients receive. The panel will present the key action statements that address patient presentation, history, and physical examination; laboratory testing; electrodiagnostic testing; diagnostic imaging; surgical decompression; oral steroids and antiviral therapy; and patient follow‐up. Case studies will also be presented to illustrate the application of the evidence‐based recommendations in clinical practice. Educational Objectives: 1) Decrease harmful variation in care for Bell's palsy patients. 2) Improve the quality of care and outcomes for Bell's palsy patients. 3) Practice accurate and efficient diagnosis of Bell's palsy, and when applicable, increase the use of appropriate counseling and rehabilitative options for patients.